Evaluating Micro-Credentials in Europe & Southeast Asia - Radziah , Adam; Costone, Manuela; Sanasi, Francesco; Sancillo, Federica (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The evolution of labour market demands, and technological advancements have driven the rise of micro-credentials as flexible alternatives to traditional higher education qualifications. Starting from policy analysis, stakeholder opinions, and best practices, this essay examines challenges and opportunities in the assessment of micro- credentials in Europe and Southeast Asia, highlighting the importance of promoting standardized definitions, quality assurance, and alignment between academia and industry.